Bispectral Circular Dichroic Coding Metasurfaces. Issue 9 (11th August 2020) - Li, Yongfeng; Pang, Yongqiang; Wang, Jiafu; Zheng, Qiqi; Zheng, Lin; Feng, Maochang; Jing, Yao; Zhang, Jieqiu; Cui, Tiejun; Qu, Shaobo
Abstract: The frequency‐dependent circular dichroism is proposed to extend the wave manipulating capability of coding metasurfaces. As a proof of concept, the bispectral circular dichroic coding metasurfaces (CDCMs) are realized using circular dichroism resonators (CDRs) implemented via introducing loss resistors into the circular polarization conversion resonators. The CDRs are distinguished into left‐handed CDRs and right‐handed CDRs. Left‐handed CDRs absorb left‐handed circularly polarized (LCP) wave and convert right‐handed circularly polarized (RCP) wave into LCP wave. Conversely, they are defined as right‐handed CDRs. Two bispectral CDRs are designed with the left‐handed (right‐handed) and right‐handed (left‐handed) working bands in 7–8.5 and 22.2–22.5 GHz, respectively. And then, 1 bit bispectral CDCM with 0101…/1010… coding sequence is designed. Simulated results indicate that the designed CDCM strongly absorb the incident LCP (RCP) waves in the frequency region 7–8.5 GHz (22.2–22.5 GHz),  but the incident RCP (LCP) waves are anomalously reflected into four beams of the LCP (RCP) waves with high efficiency. The measured results agree well with the simulations. The results in this work may provide an effective solution for the inverse and helicity‐dependent manipulation of the electromagnetic waves in two distinct frequency regions. Abstract : Resonators with opposite circular dichroism in two distinct working bands are proposed and implemented via introducing loss resistors into circular polarization conversion resonators. Bispectral circular dichroic coding metasurfaces are designed using the circular dichroism resonators. Helicity‐selective absorption and anomalous cross‐polarization reflection under CP wave illumination are realized and inverted in the two frequency regions.